Developing Digital Storytelling Materials Rooted in Local Wisdom for English Language Learning - Litha Nesidekawati Dakka; Marhamah; Wahdaniatul Mukarrama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study looked at the divide between English language materials and the local cultural context in Southeast Sulawesi. It focused on creating digital storytelling materials based on Tolaki local wisdom using the ADDIE approach, which includes Analysis, Design, Development, Implementation, and Evaluation. This research and development project involved 30 tenth-grade students at SMA Negeri 1 Tirawuta, using a quasi-experimental design. Quantitative data came from pre-tests and post-tests aligned with CEFR A2-B1 standards. Qualitative data were collected through interviews, observations, and questionnaires. The results showed a significant improvement in English language skills, with a t-value of 24.83, df of 29, and a p-value of less than 0.001. Sixty percent of students achieved A2 or higher, up from 33.3%. Thirty percent reached B1, increasing from 10%. A strong positive correlation, r=0.82 and p<0.01, existed between cultural reflection and language skills. This result confirmed that including Tolaki values, such as mepokoaso, mendulu, and kosehe, improved language accuracy and fluency. Student engagement increased, showing a mean difference of 2.5 for local wisdom, while intrinsic motivation rose from 35% to 67%, fueled by pride in their cultural heritage. Validation by cultural experts and teachers ensured authenticity, scoring 4.8 out of 5, and relevance to the curriculum, scoring 4.6 out of 5. The final products included modules, teacher guides, and multimedia elements that supported inclusive language learning and cultural preservation, creating a model that can be replicated in Indonesia’s multicultural context.